Role of CD40 ligand-mediated endothelial cell-monocyte interaction at atherosclerosis predilection sites - Lont, Sebastian Alexander; Rehberg, Franziska; Hecker, Markus; Wagner, Andreas H. (Biochemical pharmacology, 2022)
Background - Monocyte recruitment into the vessel wall at atherosclerosis predilection sites is essential for lesion development in the early phase of atherosclerosis. Platelets interacting with ultra-large von Willebrand Factor (ULVWF) multimers deposited after CD40 receptor ligation on the endothelial surface form adhesive bridges and facilitate monocyte diapedesis. We hypothesise that enhanced endothelial CD40 expression at arterial bifurcations is responsible for monocyte recruitment and that its absence reduces susceptibility to atherosclerosis. - Methods - Y-shaped channel slides covered with endothelial cells (HUVEC) and isolated perfused carotid artery bifurcations from different mouse lines were used for adhesion studies with isolated fluorescent dye-labelled platelets and monocytes. Monocyte adherence was quantified via fluorescence imaging. Oil Red O staining visualised aortic atherosclerotic plaques, and mRNA expression was determined by qRT-PCR. - Results - In response to soluble CD40 ligand (sCD40L) stimulated ULVWF release, the number of monocytes bound distal to the bifurcation of the Y-slide was 1.8-fold greater than without stimulation. The number of adherent monocytes in sCD40L-treated carotid artery bifurcations was 6 to 12.3-fold greater in ApoE knockout mice as compared to bifurcations derived from CD40/ApoE-deficient or control mice. CD40 mRNA expression was 2-fold higher in carotid artery bifurcations of ApoE knockout mice as compared to the proximal unbranched segment. Introduction of the CD40 knockout into the ApoE-/- background reduced the atherosclerosis burden along the entire aorta of these mice by 60 %. - Conclusions - Our data demonstrate the importance of endothelial CD40 expression at atherosclerosis predilection sites for endothelial cell-platelet-monocyte interaction in the early phase of atherosclerosis.